Effect of Home-Based Yoga Intervention on Lipid Profile in Hypertensive Patients - Ved Prakash, Shrikrishna Nagorao Bamne (South Eastern European Journal of Public Health, 2025)
Introduction: India has been reported to be the diabetes capital of the world and a control in lipid profile could go a long way in reducing cardiovascular adverse events in the population. The present study was aimed at assessing if home based yoga interventions could improve the lipid profile of the study participants in the intervention group. Materials and methods: The present study was a non-randomised controlled trial, conducted for a period of two years, from December 2021 to December 2023 at a tertiary care teaching institute in Indore. Total 300 participants were divided into four groups (two intervention and two control groups) that were followed up for three months to assess the changes in their lipid profile after yoga intervention in the intervention group. Results: The study participants from the intervention group reported a significant improvement in their lipid profile parameters, namely triglycerides (P <0.05), low density lipoprotein (P <0.05) and high-density lipoprotein (P <0.01). Conclusions: Yoga’s ability to improve the lipid profile makes it a promising non-pharmacological option for hypertension management